Penetration of International Economic Law in the Development of the Cyber Notary Concept in Indonesia - Lubis, Ikhsan; Murwadji, Tarsisius; Sukarja, Detania; Rosmalinda, Rosmalinda (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This study aims to describe the penetration of international economic law in the development of the cyber notary concept in Indonesia. The development of the world today, which has entered the Industrial Revolution 4.0, has forced international law to develop the idea of a cyber notary. It needs to be conducted because Indonesia has no legal instrument to regulate cyber notaries. This study adopts legal research conducted to examine the problem in a normative juridical approach where the author examines various laws and regulations because normative juridical conceptualizes law as a written norm and is poured into legislation used as a benchmark for the community. The study results indicate that various legal instruments have been established, such as legal norms regarding Cyber Notaries in Indonesia, which are contained in the Act, in particular a. Law No. 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning the Position of a Notary. Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE), Law No. 40 of 2007 concerning Limited Liability Companies.